Photocatalytic degradation of pome over lanthanum doped calcium oxide derived from cockle shells - Siti Shariah, Ghazali (2020)
Palm Oil Mill Effluent (POME) is one of the main problems faces by oil palm industry in Malaysia due to its high chemical oxygen demand (COD) and biochemical oxygen demand (BOD). Recently, photocatalysFis has been used in several studies to treat wastewater due to its ability to mineralize the organic compounds. However, the common photocatalysts used in treating POME such as titanium oxide (TiO2) and zinc oxide (ZnO) consist of metals that have limited availability. On the other hand, cockle shells have been dumped and left untreated to the environment. As one possible solution to address both environmental problems, this study utilized cockle shell as renewable feedstock of calcium carbonate which was converted to calcium oxide (CaO) that was used as photocatalyst to treat POME. Therefore, the aim of this study is to investigate the ability of cockle shell waste to be transformed to CaO to act as photocatalyst in the treatment of POME via photocatalysis reaction. Lanthanum (La) was used in this study to act as dopant to enhance the photocatalytic activity of CaO. The CaO used in this study was converted from cockle shell wastes through calcination process at 900◦C where later the sample was denoted as Ca900. Ca900 was doped with 1 wt%, 3 wt% and 5 wt% of La using wet impregnation method where the doped photocatalyst were denoted as LaCa. Then, the photocatalysts were tested on POME under UV light in batch system by varying the effect of several operational parameters such as stirring speed, photocatalyst loadings, La loadings and oxidizing agent. All fresh and spent photocatalysts powder were characterized using fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), brunauer-emmett-teller (BET), scanning electron microsopy (SEM), energy dispersion X-ray analyser (EDX), thermogravimetric analysis (TGA), inductively coupled plasma mass spectrometry (ICP-MS) and UV-Vis diffuse reflectance spectra. The results obtained from this study show that it is achievable to produce CaO from cockle shell that can be used in photocatalytic degradation of POME. Through this research, it was found that 3 wt% of LaCa with 3.0 g/L of photocatalyst loadings at 300 rpm has highest photocatalytic activity with 54% removal compared to others. However, the removal efficiency of POME increases when oxygen as oxidizing agent were used which is 66% rather than during limited oxygen condition (54%). The kinetic data of POME degradation were fitted Langmuir-Hinshelwood kinetic model as first order reaction. In conclusion, the findings of this study imply that the contaminants in POME can be greatly reduced by utilizing La doped CaO which CaO derived from cockle shell waste.